2003
DOI: 10.1016/s0735-1097(03)00926-4
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial pleiotropic vascular effects of rosuvastatin in two hypertensive models

Abstract: These results showed that rosuvastatin reduced arterial pressure in genetic hypertension and improved systemic and regional hemodynamics in both hypertensive models independently of cholesterol levels. Thus rosuvastatin improved systemic and regional hemodynamics by reducing vascular resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
59
5
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 27 publications
9
59
5
1
Order By: Relevance
“…25 These authors found a greater reduction in MAP from baseline among statin recipients (1872 vs 1271%, Po0.05), resulting in a 7 mm Hg difference in MAP between groups after 16 weeks despite equivalent MAP at baseline. These data are consistent with experimental data and retrospective studies in humans suggesting that statin use may reduce blood pressure, [13][14][15][16][17]25,26 possibly independent of their effects on serum cholesterol. 27 However, three previous blinded, randomized studies that included a total of 480 patients found no significant effect of statins on blood pressure, 18,28,29 although the confidence limits for the individual studies did not exclude a moderate antihypertensive effect of statin treatment.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…25 These authors found a greater reduction in MAP from baseline among statin recipients (1872 vs 1271%, Po0.05), resulting in a 7 mm Hg difference in MAP between groups after 16 weeks despite equivalent MAP at baseline. These data are consistent with experimental data and retrospective studies in humans suggesting that statin use may reduce blood pressure, [13][14][15][16][17]25,26 possibly independent of their effects on serum cholesterol. 27 However, three previous blinded, randomized studies that included a total of 480 patients found no significant effect of statins on blood pressure, 18,28,29 although the confidence limits for the individual studies did not exclude a moderate antihypertensive effect of statin treatment.…”
Section: Discussionsupporting
confidence: 90%
“…[7][8][9][10][11][12][13][14] What this study adds Pravastatin 40 mg daily did not reduce blood pressure or pulse pressure at any time point in 4126 survivors of myocardial infarction who were followed for more than 5 years.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…This so-called 'sympatho-inhibitory effect' may be mediated by an increase in NO production, with the upregulation of eNOS expression in the brain. 42 In another study, Susic et al 43 evaluated the effects of rosuvastatin on systemic and regional haemodynamics in two hypertensive rat models (one genetically determined, and the other hypertensive-induced via inhibition of NO synthesis). Rosuvastatin reduced arterial BP in SHR rats and decreased total peripheral resistance.…”
Section: Do Lipid Abnormalities Predict the Risk For Hypertension?mentioning
confidence: 99%
“…These experimental subgroups were as follows: HF group (untreated group), HF-R10 group (high-fat plus rosuvastatin 10 mg), HF-R20 group (high-fat plus rosuvastatin 20 mg), and HF-R40 (highfat plus rosuvastatin 40 mg). The dose of 20 mg/kg/day of rosuvastatin used in the present study is known to produce beneficial effects upon endothelial dysfunction and systemic and regional hemodynamic and has been used previously [22,23]. The doses of 10 mg/kg/day and 40 mg/kg/day of rosuvastatin have to aim to examine whether the beneficial effects of rosuvastatin are dose-dependent.…”
Section: Animals and Dietmentioning
confidence: 99%